Study of Common Pathogens in Children with Hematological Malignancies during Episodes of Febrile Neutropenias in Tanta Pediatric Oncology Unit, Egypt - adel abd elhaleim hagag (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Hematological malignancies are the types of cancers that affect blood, bone marrow and lymph nodes. The most common hematological malignancies are leukemias and lymphomas. Objective: The aim of this study is to detect common types of pathogens and their susceptibility to antibiotics and antifungal drug therapy in children with hematological malignancies during episodes of febrile neutropenias in Tanta Pediatric Oncology Unit. Patients and methods: This study was carried out on 30 children admitted to Oncology Unit, Pediatric Department, Tanta University Hospital during the period form February 2010 to February 2011. Samples were taken as follows: 1-2 ml blood samples was aseptically withdrawn by venepuncutre using a sterile syringe after disinfecting the site of injection by 70% ethyl alcohol or from oro-pharynx by sterile swabs that were introduced into infected part of oral cavity and pharynx then the swabs were gently rotated. Results: Blood and throat cultures revealed bacterial infections in 60% and fungal infections in 40% of febrile episodes during febrile neutropenias in children with hematological malignancies. The isolated organisms were: Staphylococcus aureus (33.3%), E.coli (22.2%), Pseudomonas aeruginosa (16.7%), Klebsiella (11.1%), Streptococcus viridians (11.1%) and Acinetobacter (5.6%) of bacterial isolates. All fungal isolates were Candida (100 %). Conclusions: Fungal infections is a common cause of febrile episodes during febrile neutropenias in hematological malignancies and must be taken in consideration in every case of febrile neutropenic cancer patients also gram negative is still more common than gram positive infections in Tanta Pediatric Oncology Unit.